THE INFLUENCE OF JOB CHARACTERISTICS, WORK MOTIVATION AND WORK ABILITY ON EMPLOYEES OF THE ASTAMBUL DISTRICT OFFICE, BANJAR REGENCY - Hairy Hadiannor; Abdul Kadir (SEAN Institute, 2020)
Research objectives This is For know and analyze influence Good in a way simultaneous , partial and dominant variable characteristics job (X1), variable motivation work (X2) and variables ability work (X3) against variable effectiveness performance employee (Y) at the Sub-district Office Istanbul Banjar Regency . The method used is approach quantitative with Data analysis techniques consisting of from instrument testing ( validity and reliability testing), multiple linear regression analysis , testing assumption classical ( normality test , multicollinearity test , and heteroscedasticity test ), as well as testing hypothesis (F test and T test). The sample used is 41 people or all over population . Research results show that variable Characteristics Job (X1), Motivation Work (X2) and Ability Work (X3) has an effect in a way simultaneous , variable Characteristics Job (X1) and variables Ability Work (X3) has significant and positive influence in a way partial to variable effectiveness performance (Y), then influential variables in a way domimam is variable Characteristics Job (X1).